Dynamics of the ovarian reserve and impact of genetic and epidemiological factors on age of menopause - Pelosi, Emanuele; Simonsick, Eleanor; Forabosco, Antonino; Garcia-Ortiz, Jose Elias; Schlessinger, David (Biology of reproduction, 2015)
The narrow standard age range of menopause, ∼50 yr, belies the complex balance of forces that govern the underlying formation and progressive loss of ovarian follicles (the "ovarian reserve" whose size determines the age of menopause). We show here the first quantitative graph of follicle numbers, distinguished from oocyte counts, across the reproductive lifespan, and review the current state of information about genetic and epidemiological risk factors in relation to possible preservation of reproductive capacity. In addition to structural X-chromosome changes, several genes involved in the process of follicle formation and/or maintenance are implicated in Mendelian inherited primary ovarian insufficiency (POI), with menopause before age 40. Furthermore, variants in a largely distinct cohort of reported genes-notably involved in pathways relevant to atresia, including DNA repair and cell death-have shown smaller but additive effects on the variation in timing of menopause in the normal range, early menopause (age <45), and POI. Epidemiological factors show effect sizes comparable to those of genetic factors, with smoking accounting for about 5% of the risk of early menopause, equivalent to the summed effect of the top 17 genetic variants. The identified genetic and epidemiological factors underline the importance of early detection of reproductive problems to enhance possible interventions.